EXAMINING STUDENTS' CONCEPT MASTERY AND CREATIVITY THROUGH DIGITAL STORYTELLING VIDEO IN LEARNING FOOD ADDITIVES - Weni Anissa Putri, - (2020)
Students' concept mastery and creativity were low because they have learning difficulties in classroom. Digital storytelling video is powerful tool for students who construct their own story. The aim of this research is to identify students' concept mastery and creativity through digital storytelling video in learning food additives. The method used experimental method or weak experimental method. The design of this research is one group pretest-posttest design. The sample of this research is from 8th grade of private school in Cianjur, West Java. The sample is purposive sampling. Students' creativity is measured three dimensions: novelty, resolution and elaboration and synthesis on rubric. For students' concept mastery, it is measured based on objective test. The result showed that students' concept mastery improves with N-Gain is 0.30 it is categorized as medium improvement. Highest improvement of students' concept mastery in cognitive domain C1 with N-Gain 0.33 categorized as medium. The high aspect of foods are food additives types which are (0.30) categorizes medium. Additives in human effort to reduce consuming food additives with N-Gain 0.30 indicates medium improvement than other aspects. The result of students' creativity based on three dimensions are resolution has the average score (54%) categorized as very low, revolution has average score (61%) categorized as medium. elaboration and synthesis have average score (66%) categorized as medium. Based on this result, Digital storytelling video can be used as learning tool for students' concept mastery and students' creativity.